Africville and the Dynamics of State Power in Postwar Canada - Loo, Tina (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2010)
Abstract This article examines the program of urban renewal undertaken by the City of Halifax in the mid-1960s that resulted in the destruction of the African Canadian neighbourhood of Africville. Focusing on how the relocation was carried out gives us a very different view of the workings of the postwar state – specifically, of the contingencies of power and the complexities of its exercise. Africville is important not just as an example of racism, but for what it reveals about the dynamics of state power and the meanings of the good life embedded in the welfare state.